Peer Review in Law Journals - Stojanovski, Jadranka; Sanz-Casado, Elías; Agnoloni, Tommaso; Peruginelli, Ginevra (Frontiers in Research Metrics and Analytics, 2021)
The field of law has retained its distinctiveness regarding peer review to this day, and reviews are often conducted without following standardized rules and principles. External and independent evaluation of submissions has recently become adopted by European law journals, and peer review procedures are still poorly defined, investigated, and attuned to the legal science publishing landscape. The aim of our study was to gain a better insight into current editorial policies on peer review in law journals by exploring editorial documents (instructions, guidelines, policies) issued by 119 Croatian, Italian, and Spanish law journals. We relied on automatic content analysis of 135 publicly available documents collected from the journal websites to analyze the basic features of the peer review processes, manuscript evaluation criteria, and related ethical issues using WordStat8. Differences in covered topics between the countries were compared using the chi-square test. Our findings reveal that most law journals have adopted a traditional approach, in which the editorial board manages mostly anonymized peer review (104, 77%) engaging independent/external reviewers (65, 48%). Submissions are evaluated according to their originality and relevance (113, 84%), quality of writing and presentation (94, 70%), comprehensiveness of literature references (93, 69%), and adequacy of methods (57, 42%). The main ethical issues related to peer review addressed by these journals are reviewer’s competing interests (42, 31%), plagiarism (35, 26%), and biases (30, 22%). We observed statistically significant differences between countries in mentioning key concepts such as 'peer review ethics', 'reviewer', 'transparency of identities', 'publication type', and 'research misconduct'. Spanish journals favor reviewers' 'independence' and 'competence' and 'anonymized' peer review process. Also, some manuscript types popular in one country are rarely mentioned in other countries. Even though peer review is equally conventional in all three countries, high transparency in Croatian law journals, respect for research integrity in Spanish ones, and diversity and inclusion in Italian are promising indicators of future development.